2010
DOI: 10.1007/s00382-010-0922-z
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal circulations and their multi-scale interaction leading to rainfall over the South China Sea upstream of the Philippines during intraseasonal monsoon westerly wind bursts

Abstract: The morning diurnal precipitation maximum over the coastal sea upstream of the Philippines during intraseasonal westerly wind bursts is examined from observations and numerical model simulations. A welldefined case of precipitation and large-scale circulation over the coastal sea west of the Philippines during 17-27 June 2004 is selected as a representative case. The hypothesis is that the mesoscale diurnal circulation over the Philippines and a large-scale diurnal circulation that is induced by large-scale di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…It is worth noting that the spatial extent of the land-sea breezes is not only limited in the vicinity of the coast (the local diurnal cycle), but they could reach far areas in the open sea (near 38N, 1088E, which is about 500 km away from the northwest coast of Borneo; Figs. 5a,d)-similar to the large-scale diurnal variation of winds to the west of the Philippines that is associated with the delayed surface heating/cooling over the Asian continent and IndoChina Peninsula in June 2004 (Park et al 2011). This kind of diurnal cycle of winds over the South China Sea seems stronger in WT1 (which occurs more frequently in the fall in early SON, thus with stronger surface heating over the Asian continent; Fig.…”
Section: B Weather Types and Their Frequencies And Rainfall Distribumentioning
confidence: 86%
“…It is worth noting that the spatial extent of the land-sea breezes is not only limited in the vicinity of the coast (the local diurnal cycle), but they could reach far areas in the open sea (near 38N, 1088E, which is about 500 km away from the northwest coast of Borneo; Figs. 5a,d)-similar to the large-scale diurnal variation of winds to the west of the Philippines that is associated with the delayed surface heating/cooling over the Asian continent and IndoChina Peninsula in June 2004 (Park et al 2011). This kind of diurnal cycle of winds over the South China Sea seems stronger in WT1 (which occurs more frequently in the fall in early SON, thus with stronger surface heating over the Asian continent; Fig.…”
Section: B Weather Types and Their Frequencies And Rainfall Distribumentioning
confidence: 86%
“…Observational facts of MJO have been documented by abundant studies [e.g., Li and Wu , ; Li and Zhou , ; Salby and Hendon , ; Jones and Weare , ; Maloney and Hartmann , ; Woolnough et al ., ; Fu et al ., ; Sperber , ; Jiang et al ., , ; Zhang , ; Li et al ., ] and many investigations have been conducted on its impacts on global weather and climate [ Higgins and Shi , ; Lawrence and Webster , ; Wheeler and McBride , ; Donald et al ., ; Jeong et al ., ; Wheeler et al ., ; Zhang et al ., ; Tong et al ., ; Jia et al ., ; Li et al ., ]. Compared to the MJO, less effort has been devoted to understanding the QBWO, and most previous studies of QBWO have focused on the tropical Asian monsoon region and the western North Pacific (WNP) including the South China Sea (SCS) [ Krishnamurti and Ardanuy , ; Chen and Chen , , ; Fukutomi and Yasunari , , ; Chen et al ., ; Chan et al ., ; Mao and Chan , ; Zhou and Chan , ; Wen and Zhang , ; Chen and Sui , ; Park et al ., ]. Atmospheric oscillation of 10–20 days was earliest reported in the Indian monsoon [ Krishnamurti and Ardanuy , ; Chen and Chen , ].…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of the largescale diurnal circulation over this high-latitude region is certainly different than that over the tropical ocean. In Park et al (2011), the large-scale diurnal circulation is not highly correlated with the diurnal variation in precipitation; the essential role of the local diurnal circulation, as well as the large-scale effect on the diurnal variation in precipitation, was explored over the tropical ocean using MM5 simulations.…”
Section: Large-scale Diurnal Effectsmentioning
confidence: 99%
“…The present study further broadens the domain to 145°E to include the coastal sea of Japan. Several studies suggested that the large-scale diurnal circulation on the scale of thousands of kilometers is critical in modulating precipitation during the South Asian monsoon (Krishnamurti and Kishtawal 2000;Chow and Chan 2009;Park et al 2011). Park et al (2011 showed that the interaction between the large-scale diurnal circulation and the local land-sea breezes induces the diurnal peak in rainfall over the western coastal sea of the Philippines.…”
Section: Introductionmentioning
confidence: 99%